Wheat Carbon Dioxide Responses in Space Simulations Conducted at the Chinese Lunar Palace‐1. (1st January 2016) - Dong, Chen; Shao, Lingzhi; Wang, Minjuan; Liu, Guanghui; Liu, Hui; Xie, Beizhen; Li, Bowei; Fu, Yuming; Liu, Hong
Abstract : Since the industrial revolution, anthropogenic activities, such as fossil fuel use and deforestation, have caused a dramatic increase in the atmospheric CO2 concentration. To understand how the growth and development in cereal crops may respond to elevated CO2, it is necessary to determine if the leaves of crops grown in a closed artificial ecosystem have a fully developed photosynthetic apparatus and whether or not photosynthesis in these leaves is more responsive to an elevated CO2 concentration. To address this issue, we evaluated the response of the photosynthetic characteristics, antioxidant capacity, and water use efficiency of wheat ( Triticum aestivum L.) under four CO2 concentrations (500, 1000, 3000, and 5000 ppm) for 3 d in Lunar Palace‐1, which is the first bioregenerative life support system developed in China. The results showed that wheat cultivated at 1000 ppm from vegetative growth to maturity was characterized by more appropriate relative water content, membrane stability index, photosynthetic rate, chlorophyll concentration, and antioxidant capacity, which was more beneficial to growth and development in a closed artificial environment. There were significant effects with increased CO2 concentration on the effective quantum yield of PSII and photosynthetic electron transport of wheat plants. Furthermore, elevated CO2 controlled the transpiration rate, which enhanced water use efficiency. During ripening, wheat aging may be accelerated by elevated CO2, which promotes grain growth and maturing.